Nivolumab plus ipilimumab plus cabozantinib triplet combination for patients with previously untreated advanced renal cell carcinoma: Results from a discontinued arm of the phase III CheckMate 9ER trial. (December 2022) - Apolo, Andrea B.; Powles, Thomas; Escudier, Bernard; Burotto, Mauricio; Zhang, Joshua; Simsek, Burcin; Scheffold, Christian; Motzer, Robert J.; Choueiri, Toni K.
Abstract: Background: The phase III CheckMate 9ER trial originally included a nivolumab plus ipilimumab plus cabozantinib triplet arm, which was discontinued early due to the evolving treatment landscape for first-line advanced renal cell carcinoma (aRCC). We report an exploratory analysis of patients randomised to the triplet regimen before enrolment discontinuation. Methods: Patients with clear-cell aRCC received nivolumab (3 mg/kg) plus ipilimumab (1 mg/kg) Q3W for four cycles with once-daily cabozantinib (40 mg), then nivolumab (240 mg) Q2W plus once-daily cabozantinib (40 mg). CheckMate 9ER primary (progression-free survival [PFS] by blinded independent central review [BICR]) and key secondary (overall survival [OS], objective response rate [ORR] by BICR, and safety) endpoints were applied, along with investigator-assessed PFS and ORR. Results: Fifty patients were randomised to the triplet regimen. After a median follow-up of 39.1 months (range, 33.4–44.5), median PFS (95% CI) was 9.9 (5.7–16.8) months by BICR and 13.9 (7.3–24.7) months by investigator; median OS (95% CI) was 37.0 (31.8-not estimable) months. ORR (95% CI) was 44.0% (30.0–58.7; complete response, 8.0%) by BICR and 48.0% (33.7–62.6; all partial responses) by investigator. Grade 3–4 treatment-related adverse events (TRAEs) occurred in 84.0%, most commonly alanine aminotransferase increased (20.0%), aspartate aminotransferase increased (16.0%), and hepatotoxicity (16.0%). Grade 3–4 hepatic immune-mediated AEs occurred in 40.0%. There were no grade 5 TRAEs. Conclusions: These results suggest that the nivolumab plus ipilimumab plus cabozantinib triplet combination has clinical activity in patients with previously untreated aRCC, although monitoring of overlapping toxicities will be important in future studies of this regimen. ClinicalTrials.gov registration: NCT03141177. Highlights: Nivolumab + ipilimumab + cabozantinib has clinical activity in untreated aRCC. Monitoring overlapping toxicities will be important in future studies. Evaluation of the triplet regimen is ongoing in the phase III COSMIC-313 trial.